ICT-based integrated framework for smart facility management: an industry perspective. Issue 5 (13th September 2021) - Sulaiman, Mohammed; Sulaiman, Mohammed; Liu, Hexu; Binalhaj, Mohamed; Al-Kasasbeh, Maha; Abudayyeh, Osama
Abstract : Purpose: Current facility management (FM) practices are inefficient and ineffective, partially because of missing information and communication issues. Information and communications technologies (ICT) are asserted to provide a promising solution for managing and operating facilities. However, the impact of ICT applications on current FM practices needs to be validated and the perception of FM professionals on ICT-based FM needs to be understood. Therefore, this paper aims to investigate the impacts and the perception of ICT application on FM practice and further develop an ICT-based integrated framework for smart FM practices. Design/methodology/approach: To achieve the objective, the research starts with reviewing several promising ICT for FM, including building information modeling, geographic information systems, unmanned aerial vehicle and augmented reality. On this basis, a conceptional framework was synthesized in consideration of the benefits of each technology. A survey questionnaire to FM professionals was conducted to evaluate the proposed framework and identify the challenges of adopting ICT in the FM industry. Furthermore, return on investment and strength, weakness, opportunities and threats analysis have been used in this paper as evaluation methods for ICT industry adoption. Findings: The survey results are validated by FM professionals for the future engagement of the integrated ICT applications. Also, the proposed framework can assist the decision-makers to have comprehensive information about facilities and systematize the communication among stakeholders. Originality/value: This research provides an integrated framework for smart FM to improve decision-making, capitalizing on the ICT applications. Apart from this, the study sheds light on future research endeavors for other ICT applications.